Mechanical and Physical Properties of Bio-Briquette Produced from Gayo Arabica Coffee-Skin - Adi Setiawan; Juwaini; Ahmad Nayan; Fauzan; Faisal (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Enormous amount of Gayo Arabica coffee-by-products highlights its potential as source of renewable energy. Utilizing coffee skin as a raw material for bio-briquettes is considered as an effective way to minimize their wastage as landfill. This study aims to examine the characteristics of bio-briquettes produced through the cold-forming process at a pressure of 100, 150 and 200 kg/cm2 without binder. Prior to briquetting process, the raw material was sun-dried, ground and sieved to 0.841 mm. A mixture was then made by adding water followed by molding and drying processes. Characterization of the briquette employs a number of techniques including DSC, TGA, bomb calorimeter and proximate analyses as well as mechanical testing. The results show that the calorific value of the coffee-skin briquette is 4764 cal/g containing 16.5 wt% of moisture, 12 wt.% ash. The rate of combustion is 0.019 g/s with ignition time of 196 s. Varying briquetting pressure results in a change in ignition time of bio-briquettes as the density is increased. However, no significant change was observed on the rate of combustion upon increasing the briquetting pressure. This investigation concludes the potential use of coffee industry by-product as feedstock for solid